Oleadas impetuosas y arenas movedizas: diplomacia y lecturas sudamericanas de la expropiación petrolera mexicana, circa 1938 - Zuleta, María Cecilia (Universidad del Pacífico, 2011)
Exploring the reception of Mexican oil expropriation, in 1938, by South American diplomacy and public opinion, is the aim of this essay. Propaganda, diffusion and reception of the Mexican oil matter at the expropriation juncture are studied, focusing only on Southern Cone countries and Bolivia. To reach this purpose, it’s showed a synthetic revision of diplomatic and press repercussions, as well as a brief description of politic reactions and expressions of public and popular support at those countries. It can be argued that, even though the Mexican government propaganda efforts were too impetuous to legitimize President Lázaro Cárdenas oil companies’ expropriation at the Latin American countries, the results ran into a wide range of reactions. It depends on the political, social or economic situation of each country: sometimes propaganda came to a halt. Nevertheless, these propaganda efforts developed Mexican interactions with Argentina, Bolivia, Chile and Uruguay. And, in spite of quicksand of diplomacy, Mexican petroleum nationalism was reinterpreted by South Americans leaving important historical marks.